Tell me about your Day: Portraying Students Reflective Practice through Diary Writing - Kasprabowo, Teguh; Rahayu, Endang Yuliani; Widyaningrum, Agnes (Universitas Negeri Semarang, 2021)
Although commonly understood that diary writing benefits language learners in many ways, the use of diary writing as a medium for reflective practice in higher education is still rarely considered. The study aimed to portray the student's reflective practice through diary writing - to display how the student made meaning of her daily life and learning experiences. Employing qualitative case study, we observed one of our students reflective practice through her diary entries. Our study employed Rodgers summary of Deweys reflective practice (2019) as the theoretical framework. The data of this research was a handwritten diary of a student named Lana containing 30 diary entries written from September 6, 2018, to October 22, 2018. The entries were written in the period when she joined a Creative Writing class. The diary writing activity was mainly aimed to help the students in the class to build their writing habits by writing reflections of their daily activities. The result showed that diary writing provided room for Lana to carry out the reflective practice. This practice helped her to see and to understand herself as a learner. Also, Lana specifically expressed that diary writing helped her to have ideas for writing easily. Based on the findings, we argue that in the Indonesian higher education context diary writing needs to be incorporated in the learning process to benefit learners in their personal development and their language learning process.